Approach to Critical Crack Opening Displacement Modeling of Damage in Metal Sheets after Composite Patch Bonded Repair - Sałacinski Michał; Leski Andrzej; Stefaniuk Michał (Fatigue of Aircraft Structures, 2016)
The paper proposes a method of calculating the maximum displacement in the aircraft metal structure repaired by CPBR (bonded composite patch repair).